Women's career development in an Arab Middle Eastern context. Issue 2 (15th March 2019) - Abalkhail, Jouharah M.
ABSTRACT: This study examines women's perspectives on requirements for enabling their access to senior leadership roles in the under-researched context of the Arab Middle East. It draws on an approach that utilizes qualitative, in-depth, semi-structured interviews with academic women working in Saudi Arabia higher education. The findings of this study reveal several culturally responsive strategies for supporting the advancement of women into leading positions within higher education. Also, the study demonstrates how women in Saudi higher education learn to resist patriarchal power structures and gender discrimination, and to develop their own strategies for negotiating those issues. In addition, the results provide evidence of the academy's importance as an institution that works collaboratively with the government to develop women's careers. The originality of this paper is its contribution to the limited knowledge that currently exists on women's career development in the Arab Middle Eastern context. This study also will benefit human resource departments and human resource development practitioners with knowledge regarding the intertwining of social forces with university practices, and gender-related issues, which in turn affect women's positions in the academy. Additionally, the study suggests that human resource development practitioners should establish policies and practices with respect to gender-related equity issues that could have a positive impact on wider national human resource development systems, and potentially open more opportunities for positive career development for women.